Multiwavelength magnetic coding of helical luminescence in ferromagnetic 2D layered CrI3 - Bo Peng; Zhiyong Chen; Yue Li; Zhen Liu; Difei Liang; Longjiang Deng (iScience, 2022)
Summary: Two-dimensional (2D) van der Waals (vdW) ferromagnets have opened new avenues for manipulating spin at the limits of single or few atomic layers, and for creating unique magneto-exciton devices through the coupling of ferromagnetic (FM) orders and excitons. However, 2D vdW ferromagnets explored so far have rarely possessed exciton behaviors; to date, FM CrI3 have been revealed to show ligand-field photoluminescence correlated with FM ordering, but typically with a broad emission peak. Here, we report a straightforward approach to realize strong coupling of narrow helical emission and FM orders in CrI3 through microsphere cavity. The resonant whispering-gallery modes (WGM) of SiO2 microspheres cause strong oscillation helical emissions with a full width at half-maximum (FWHM) of ∼5 nm under continuous wave excitation. Reversible magnetic coding of helical luminescence is realized in the range of 950–1100 nm. This work enables numerous opportunities for creating magnetic encoding lasing for photonic integrated chips.